Rejection of Armenian genocide allegations by international courts - YALÇINKAYA, ALAEDDİN (ISRES Publishing, 2023)
According to Article 6 of the Convention on the Prevention and Punishment of Genocide,genocide can only be determined by a court decision. However, Armenian genocideclaimants have refrained from applying to international courts as required. However,many national and international courts have determined that the allegations in questionhave no legal basis. The court decisions summarized in this section, which were filedindirectly, clearly reject Armenian genocide allegations.The most prominent of these is the acquittal decision of the British Crown Prosecutor’sOffice regarding the Malta Exiles in 1921, six years after the 1915 deportation. Afterthe acceptance of Türkiye’s EU candidate status, these allegations were rejected by thefirst instance and Grand Chamber decisions filed by Armenians in the Court of Justiceof EU. According to the first instance and Grand Chamber decisions of the EuropeanCourt of Human Rights in the Perinçek-Switzerland case, it was stated that denying theArmenian genocide allegations cannot be a crime because there is no final court decisionon this issue. The decisions of the French Constitutional Council summarized above areimportant in terms of impartiality and legality in judicial decisions, despite the strongArmenian lobby and anti-Türkiye sentiment, even though they are decisions of a nationalcourt outside Türkiye. A similar situation also applies to the British Crown Prosecutor’sdecision regarding the Maltese exiles. The Court of Justice of the European Union andthe ECHR are international judicial bodies, and both are the courts of societies whereanti-Türkiye sentiment and the Armenian lobby are significantly active. All these courtsrejected the Armenian genocide allegations and not any court decision was given to thecontrary.

According to Article 6 of the Convention on the Prevention and Punishment of Genocide,genocide can only be determined by a court decision. However, Armenian genocideclaimants have refrained from applying to international courts as required. However,many national and international courts have determined that the allegations in questionhave no legal basis. The court decisions summarized in this section, which were filedindirectly, clearly reject Armenian genocide allegations.The most prominent of these is the acquittal decision of the British Crown Prosecutor’sOffice regarding the Malta Exiles in 1921, six years after the 1915 deportation. Afterthe acceptance of Türkiye’s EU candidate status, these allegations were rejected by thefirst instance and Grand Chamber decisions filed by Armenians in the Court of Justiceof EU. According to the first instance and Grand Chamber decisions of the EuropeanCourt of Human Rights in the Perinçek-Switzerland case, it was stated that denying theArmenian genocide allegations cannot be a crime because there is no final court decisionon this issue. The decisions of the French Constitutional Council summarized above areimportant in terms of impartiality and legality in judicial decisions, despite the strongArmenian lobby and anti-Türkiye sentiment, even though they are decisions of a nationalcourt outside Türkiye. A similar situation also applies to the British Crown Prosecutor’sdecision regarding the Maltese exiles. The Court of Justice of the European Union andthe ECHR are international judicial bodies, and both are the courts of societies whereanti-Türkiye sentiment and the Armenian lobby are significantly active. All these courtsrejected the Armenian genocide allegations and not any court decision was given to the contrary.
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Uyuşmazlık Analizi ve Çözümü; Social Sciences and Humanities; Political Science; Conflict Analysis and Resolution; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; Social Sciences & Humanities